Our experience regarding patients with headache, vomiting, and urinary retention following endothermal ablation of the greater saphenous vein under spinal anesthesia: Gender type, age interval, and procedural risk factors are important. (October 2020) - Bitargil, Macit; El Kılıç, Helin
Objectives: The endovenous thermal ablation of the greater saphenous vein under spinal anesthesia is still a popular technique. Although this procedure is considered to be fast and simple, side effects such as headaches, vomiting, and urinary retention could occur. These side effects make the recovery period difficult for the patient. The patient's age, gender, and procedural risk factors such as needle sizes and types are important parameters that affect the occurrence and rate of undesirable outcomes. This retrospective study aims to evaluate the endovenous thermal ablation method for the management of incompetent great saphenous veins under spinal anesthesia. Methods: A total of 128 patients with incompetent varicose veins who were treated with an endovenous thermal ablation method under spinal anesthesia were retrospectively investigated between January 2016 and January 2019. The pre-, intra-, post-procedural, and follow-up data of the patients were collected and retrospectively compared. Results: A total of 128 patients (69 males, 59 females; mean age 45.8 ± 11.8 years; range 21–71 years) were included in the study. The average preprocedural great saphenous vein diameters were 7.41 ± 18.8 mm (range: 5.5–13.0). The average ablated vein length was 25.3 ± 3.4 (range: 15–35) cm. The average tumescent anesthesia use was 300.9 ± 52.6 (range: 150–500) mL. The average procedure time was 18.2 ± 1.8 (range: 11–25) min. The venous clinical severity scores and the chronic venous insufficiency quality of life questionnaire scores declined significantly ( p for venous clinical severity scores: 0.001, p for chronic venous insufficiency quality of life questionnaire scores: 0.001). There was no postoperative paresis or paresthesia. There was one case of deep venous thrombosis and three cases of bruising. The total of three months' occlusion rates was 96.9% (124/128). The overall post-dural puncture headache ratio was 18%. Women significantly suffered from more headaches than men (27% vs. 10%, p  = 0.013). The extreme age intervals (pertaining to ages between 18 and 30 or 50 + ) were almost significantly less affected by headaches in comparison to the group with the age interval between 31 and 50 (11.3%, 24.2%, p : 0.056). A percentage of 12.5 patients suffered from vomiting. It was recorded that female patients suffered from vomiting more so than the males (20.3%, 5.8%, p : 0.013). Pertaining to vomiting, there was no significant difference between the two age interval groups ( p : 0.14). Urinary retention was observed in 6.3% of the patients. The female gender had a higher ratio of urinary retention, but the difference was insignificant. (8.5%, 4.3%, p : 0.46). There was no significant difference between the age interval groups in terms of urinary retention. Conclusions: The endovenous thermal ablation of the greater saphenous vein under spinal anesthesia is a fast and effective treatment option for the management of incompetent saphenous veins. However, side effects such as headaches, vomiting, and urinary retention that are affected by gender types, age-intervals, and procedural characteristics should be kept in mind.